Multicenter study on the effect of nonsteroidal anti‐inflammatory drugs on postoperative pain after endoscopic sinus and nasal surgery. Issue 4 (13th December 2019) - Wu, Arthur W.; Walgama, Evan S.; Genç, Ege; Ting, Jonathan Y.; Illing, Elisa A.; Shipchandler, Taha Z.; Higgins, Thomas S.
Abstract : Background: The taboo of avoiding nonsteroidal anti‐inflammatory drugs (NSAIDs) after functional endoscopic sinus surgery (FESS) has been waning. The impetus to reduce opioid prescriptions in view of the opioid epidemic led the authors to change their practices to include NSAIDs after sinus surgery. This study's aim was to analyze the differences between patients before and after we began recommending NSAIDs after FESS. Methods: A prospective cohort study was performed on patients undergoing FESS or other endoscopic nasal surgeries at 3 institutions, by 5 rhinologists and 1 facial plastic surgeon. Before introducing NSAIDs, all patients were given a prescription for hydrocodone‐acetaminophen 5/325 mg and also recommended preferentially to use acetaminophen 325 mg. After the addition of NSAIDs, ibuprofen 200 mg and acetaminophen 325 mg were recommended preferentially, using the narcotic as a rescue medication. Patients kept a pain diary and medication log, and gave a visual analog scale (VAS) score for overall pain. Demographics, surgical variables, and comorbidities were also analyzed. Results: One hundred sixty‐six total patients were recruited and had data that could be analyzed (65 without NSAIDs, 101 with NSAIDs). Overall, mean pain VAS score was 3.12 ± 1.95 for the non‐NSAID group and 2.33 ± 2.30 for the NSAID group ( p value = 0.006). The day with the highest mean pain was the first postoperative day. The mean number of total opioid pills taken was 6.94 ± 6.85 without NSAIDs vs 3.77 ± 4.56 with NSAIDs ( p = 0.018). Age and gender were found to be the only consistently significant patient variables to affect pain. There were no bleeding complications. Conclusion: NSAID use was introduced into the practices of 5 practicing rhinologists and 1 facial plastic surgeon. No bleeding complications were seen. Both pain and overall opioid usage were reduced significantly.